Pathological complete response with nivolumab for recurrence of liver metastasis after gastrectomy of gastric cancer - Chen Jun; Suguru Yamauchi; Yukinori Yube; Hiroki Egawa; Yutaro Yoshimoto; Akira Kubota; Kenki Tsuda; Sanae Kaji; Hajime Orita; Shinichi Oka; Shinji Mine; Tetsu Fukunaga (Surgical Case Reports, 2023)
Abstract Background Advanced gastric cancer has an unfavorable prognosis and poor curability. Immune checkpoint inhibitors, such as nivolumab, have recently emerged as a potential solution for this aggressive disease. However, there is a lack of established evidence on the clinical efficacy of these agents, particularly in the perioperative period for advanced gastric cancer patients who are unresectable, recurrent, or preoperative. Despite the limited data available, there have been rare cases of dramatic therapeutic effects. In this study, we present a successful case of nivolumab treatment along with surgery. Case presentation A 69-year-old female presented with pericardial discomfort and was diagnosed with advanced gastric cancer following upper gastrointestinal endoscopy. Laparoscopic distal gastrectomy with D2 lymph node dissection was performed, resulting in a final pathological diagnosis of Stage IIIA. The patient received postoperative adjuvant chemotherapy with oral S-1 therapy, but was found to have multiple liver metastases at 8 months postsurgery. Weekly paclitaxel and ramucirumab therapy was initiated, but the patient experienced adverse side effects, leading to the discontinuation of treatment. Nivolumab monotherapy was then administered for 18 cycles, resulting in a partial therapeutic response and PET–CT revealed a complete metabolic response. However, the patient developed a Grade 3 pemphigoid as an immune-related adverse event, leading to the cessation of nivolumab. The patient underwent laparoscopic partial hepatectomy. Postoperative pathology showed no residual tumor cells, indicating a complete response. At present, 25 months after surgery, the patient was alive without recurrence. Conclusion In this report, we present a case of gastric cancer with liver metastatic recurrence, in which a complete pathological response was achieved with nivolumab treatment. Although determining whether surgical intervention is necessary following successful drug treatment can be challenging, PET–CT imaging may be useful in decision-making regarding surgical treatment.